Examining the factors of stress among policeman in IPK Kuantan / Nurfarhanah Nadhrah Roslan and Norfatin Izaty Padzli - Roslan, Nurfarhanah Nadhrah; Padzli, Norfatin Izaty (2013)
This study aims to examine the factors of stress among policeman in IPK Kuantan. Stress is defined as a mental and physical condition which affects an individual 's productivity, effectiveness, personal health and quality of health. The samples of this study were given to 45 respondents consists of traffic department, narcotic department, and criminal department comprising staff at IPK Kuantan. However, there are only 40 respondents who responded to our questionnaires. The results showed a significant of stress between the factors such as conflict with co-workers and work injuries. From our findings, we found that there is no significant between male and female in perceived stress and no significant between those departments in perceived stress.